Eco-physiological responses of copepods and pteropods to ocean warming and acidification - J. Engström-Öst; O. Glippa; R. A. Feely; M. Kanerva; J. E. Keister; S. R. Alin; B. R. Carter; A. K. McLaskey; K. A. Vuori; N. Bednaršek (Nature Publishing Group, 2022)
We compare physiological responses of the crustacean copepod Calanus pacificus and pelagic pteropod mollusk Limacina helicina to ocean temperatures and pH by measuring biomarkers of oxidative stress, antioxidant defences, and the activity of the respiratory electron transport system in organisms collected on the 2016 West Coast Ocean Acidification cruise in the California Current System. Copepods and pteropods exhibited strong but divergent responses in the same habitat; copepods had higher oxygen-reactive absorbance capacity, glutathione-S-transferase, and total glutathione content. The ratio between reduced to oxidised glutathione was higher in copepods than in pteropods, indicating lower oxidative stress in copepods. Pteropods showed higher activities of glutathione reductase, catalase, and lipid peroxidation, indicating increased antioxidant defences and oxidative stress. Thus, the antioxidant defence system of the copepods has a greater capacity to respond to oxidative stress, while pteropods already face severe stress and show limited capacity to deal with further changes. The results suggest that copepods have higher adaptive potential, owing to their stronger vertical migration behaviour and efficient glutathione metabolism, whereas pteropods run the risk of oxidative stress and mortality under high CO2 conditions. Our results provide a unique dataset and evidence of stress-inducing mechanisms behind pteropod ocean acidification responses.